Enhancing Students’ Learning Outcomes through MALL in English Intensive Program for Railway Mechanical Technology - Damar Isti Pratiwi; Rengganis Siwi Amumpuni; Ainun Fikria; Riana Eka Budiastuti (International Journal of Language Education, 2023)
This study attempts to investigate students’ learning outcomes in English Intensive Program through Mobile Assisted Language Learning (MALL) for Railway Mechanical Technology. The program was designed as a TOEFL preparation class that utilized Google Form, Quizizz, and Kahoot! As game-based learning (MALL platform). It was a case study on the 3rd year students of the Indonesian Railway Polytechnic (N=46). The observation was conducted during 20 meetings (40 hours). The data were collected through pre-test and post-test, then analyzed using descriptive statistics, paired t-test, Pearson r correlation, and Cohen d effect size. The passing grade score determined by the college (480) was also an additional consideration analysis. The results indicate significant impacts and a large effect on students’ learning outcomes after joining the English Intensive Program through MALL. Nonetheless, the English Intensive Program implementing MALL had a moderate correlation and was less effective in enhancing students’ learning outcomes. These findings shed light on the benefits and constraints of implementing MALL in the English Intensive Program.